The effectiveness of an educational program offered in swimming and its effect on improving the attention deficit hyperactivity disorder in autistic children - Harbach, Brahim; Sifi, Belkacem; Zabchi, Noureddine; Mokrani, Djamel (Quality in Sport, 2022)
The study aims to know the effect of an educational program in the ABCs of swimming on the improvement of the indicator of attention deficit hyperactivity disorder in autistic children, and to answer this problem, we used a case study approach 10 children aged 4–10 years old who had been diagnosed with both autism spectrum disorder and ADHD by outside psychologists, and the duration of the swimming educational program lasted ten weeks with two lessons per week. As a study tool, we relied on the Attention Deficit Hyperactivity Disorder Scale (Essalem, 2020) with an emphasis on the attention part, and after analyzing the data, we concluded that the autistic child improved most of the indicators under study and this is confirmed by other studies in the same specialty, and that is why he recommends Researchers should swim regularly for autistic children.